2008
DOI: 10.1007/s11356-008-0006-3
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of an efficient separation method for chemicals in diesel exhaust particles: analysis for nitrophenols

Abstract: The present method involving an acid-base extraction, in situ derivatization, and GC-MS analysis has shown to be a simple, efficient, and reliable method for the isolation and identification of the chemical substances in DEP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 32 publications
(16 citation statements)
references
References 33 publications
0
16
0
Order By: Relevance
“…They are thus amenable to separation by using a conventional acid-base extraction procedure. Based on this concept, we have developed the new fractionation scheme used for this work (Noya et al 2008). The sodium bicarbonate extract obtained by this procedure has been shown to contain various aromatic carboxylic acids including the new vasodilatory nitro-compounds, 4-hydroxy-3-nitrobenzoic acid (8) and 3-hyroxy-4-nitrobenzoic acid (9).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are thus amenable to separation by using a conventional acid-base extraction procedure. Based on this concept, we have developed the new fractionation scheme used for this work (Noya et al 2008). The sodium bicarbonate extract obtained by this procedure has been shown to contain various aromatic carboxylic acids including the new vasodilatory nitro-compounds, 4-hydroxy-3-nitrobenzoic acid (8) and 3-hyroxy-4-nitrobenzoic acid (9).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it was crucial to develop a more efficient and reliable method for the isolation of biologically significant components in DEP. Recently we reported an alternative protocol entailing successive extraction with water, sodium bicarbonate, and sodium hydroxide (Noya et al 2008). Analysis of the sodium hydroxide extract revealed that vasodilatory active nitrophenols are present in DEP in significantly higher amounts than estimated by a previous method involving successive solvent polarity-based extractions, followed by repeated column chromatography.…”
Section: Introductionmentioning
confidence: 97%
“…One kg of diesel exhaust particles contains an average of 52 mg PNMPP. 22) Diesel exhaust particles are stable in the environment and are considered to be one of the main airborne pollutants in urban areas, but the mechanism of PNMPP-induced toxicity is unclear.…”
mentioning
confidence: 99%
“…Nevertheless, it is considered to be hazardous waste and a priority toxic pollutant by the the U.S. Environmental Protection Agency (EPA). Recently, it has been found that 1 kg of DEP contains an average of 169 mg PNP [19]. PNP can damage the central nervous system, liver, kidney and blood of humans and animals [20].…”
mentioning
confidence: 99%